Squamous cell carcinoma of the vulva with bulky positive groin nodes—nodal debulking versus full groin dissection prior to radiation therapy. Issue 1 (1st January 2007) - Hyde, S. E.; Valmadre, S.; Hacker, N. F.; Schilthuis, M. S.; Grant, P. T.; Velden, J. Van Der
Abstract : Patients with clinical palpable involved groin lymph nodes and squamous cell cancer of the vulva are frequently treated by a full inguinal-femoral lymph node dissection followed by adjuvant radiotherapy to the groins and pelvis. Theoretically, less radical surgery for the groin such as nodal debulking, where only the macroscopically involved nodes are resected, allowing radiotherapy to treat any remaining microscopic disease may potentially decrease morbidity without compromising survival The objective of this retrospective study was to compare the groin recurrence rate and survival (disease specific and overall survival) of patients with clinically involved groin nodes and squamous cell carcinoma of the vulva treated either by a full inguino-femoral lymphadenectomy or by a nodal debulking followed by radiotherapy. Forty patients from three separate databases who met these criteria were identified. Patients were treated either by a full inguino-femoral lymphadenectomy or by a debulking of the clinically involved inguinal lymph nodes. All patients received adjuvant radiotherapy to the groins. In these two groups, there was no difference in groin recurrence rate expressed as groin recurrence-free survival ( P = 0.247). In a univariate analysis, both overall and disease-free survival were better in the group of patients treated by nodal debulking. However, in a multivariate analysis, other variables such as extracapsular growth were independent predictors for survival while the method of surgical dissection for the groin had no independent significant impact on survival.